Analysis of Business Process Management Principles in Performing Remote Audit at the Audit Board of the Republic of Indonesia - Nurlaeli, Suci; Pramono, Agus Joko (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
The Audit Board of the Republic of Indonesia must quickly adapt to its duties in the COVID-19 pandemic era. BPK forced all work to be done remotely. This study aims to analyze the application of Business Process Management Principles (BPM) in conducting remote audits at BPK following the COVID-19 pandemic. This study applies the descriptive qualitative with study literature and Likert survey on seven representative offices of BPK. The analytical tool used is BPM Principles with pattern matching. The results show that BPM principles in the remote audit have accomplished various implementation qualities. The result is divided into two types: principles that have worked properly and principles that have not maximally worked. The appropriately worked principles are context awareness, enablement, holism, continuity, institutionalization, purpose, and technology appropriation. The BPM principles that have been implemented but not maximized are the principle of involvement, the principle of joint understanding, and the principle of simplicity. Remote audits can only be conducted smoothly if all principles are implemented accordingly.